2017
DOI: 10.1073/pnas.1614664114
|View full text |Cite
|
Sign up to set email alerts
|

ERRα induces H3K9 demethylation by LSD1 to promote cell invasion

Abstract: Lysine Specific Demethylase 1 (LSD1) removes mono- and dimethyl groups from lysine 4 of histone H3 (H3K4) or H3K9, resulting in repressive or activating (respectively) transcriptional histone marks. The mechanisms that control the balance between these two antagonist activities are not understood. We here show that LSD1 and the orphan nuclear receptor estrogen-related receptor α (ERRα) display commonly activated genes. Transcriptional activation by LSD1 and ERRα involves H3K9 demethylation at the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 62 publications
2
72
0
Order By: Relevance
“…ERRα binding to a proximal (prox), but not to distal (dist) element of its own human promoter was used as positive and negative controls, respectively ( Fig. 4J) [32,33]. In the absence of added RankL, migration of 4T1-ERRα cells was lower than that of 4T1-CT cells (P = 0.0019), but the opposite was observed after Rankl treatment (P = 0.002: 4T1-CT +Rankl versus 4T1-ERRα+Rankl).…”
Section: Errα Regulates Rank Expression In Bca Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERRα binding to a proximal (prox), but not to distal (dist) element of its own human promoter was used as positive and negative controls, respectively ( Fig. 4J) [32,33]. In the absence of added RankL, migration of 4T1-ERRα cells was lower than that of 4T1-CT cells (P = 0.0019), but the opposite was observed after Rankl treatment (P = 0.002: 4T1-CT +Rankl versus 4T1-ERRα+Rankl).…”
Section: Errα Regulates Rank Expression In Bca Cellsmentioning
confidence: 99%
“…Quantification of ChIP enrichment was calculated relative to input values. Distal and proximal elements of ERRα gene were used as negative and positive controls, respectively ( Supplementary Table S7) [32,33].…”
Section: Chromatine Immunoprecipitation (Chip)mentioning
confidence: 99%
“…Most of the efforts to understand the function and specificity of TFs was so far focused on their interaction with regulatory proteins at cis-regulatory modules, so-called enhancers and promoters [5][6][7][8] . However, TFs do not only interact with other TFs but with a variety of proteins including chromatin associated proteins, histone modifiers, factors of the general transcriptional machinery or mRNA regulatory proteins [9][10][11][12][13] . Hence, it is thought that TFs promote cell type diversity by assembling protein interaction networks consisting of different types of proteins in a cell-type-specific manner 6,14,15 .…”
mentioning
confidence: 99%
“…Of note is that this phenomenon occurred to a higher extent in the basal-like model than in the luminal A model. Recently, Battaglia et al reported that LSD-1 mediated the epigenetic corruption of vitamin D signaling in prostate cancer [26], and Carnesecchi et al reported a close interaction between ERRα and LSD1 to regulate each other, mostly in cancer cell invasive behavior [27,28]. In particular, LSD-1 was involved in the maintenance of ERRα protein stability, while the ERRα protein induced LSD-1 to erase repressive marks in vitro, thereby promoting the transcriptional activation of genes involved in the invasion of the extracellular matrix.…”
Section: Errα Loss Of Function Abrogated Vdr Genomic Action On Cyp24amentioning
confidence: 99%
“…Astninski et al, indeed, demonstrated that the induction of CYP24A1 by fasting was regulated through a peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α)-ERRα-dependent mechanism, showing, for the rst time, a role for ERRα in the suppression of vitamin D signaling. Among interactors of VDR, Battaglia et al [26] highlighted the role of Lysine-speci c demethylase 1A (LSD-1), also known as KDM1A, in the corruption of VDR activity in prostate cancer, and Carnesecchi et al [27,28] reported a close interaction between ERRα and LSD-1 to regulate each other, mostly in aggressive cancers. Collectively, these ndings prompted us to evaluate the function of ERRα in the corruption of the VDR signaling network in breast cancer in vitro and through a bioinformatics approach to explore the relevant interactions underlying the biological behavior of ERRα.…”
Section: Introductionmentioning
confidence: 99%